Effect of occlusal coverage depths on the precision of 3D-printed orthognathic surgical splints - Yipeng Wang; Peiqi Wang; Xiang Xiang; Hui Xu; Yuting Tang; Yumeng Zhou; Ding Bai; Chaoran Xue (BMC Oral Health, 2022)
Abstract Background Precise orthognathic surgical splints are important in surgical-orthodontic treatment. This study aimed to propose a standardized protocol for three-dimensional (3D)-printed splints and assess the precision of splints with different occlusal coverage on the dentition (occlusal coverage depth, OCD), thus optimizing the design of 3D-printed splints to minimize the seemingly unavoidable systematic errors. Methods Resin models in optimal occlusion from 19 patients were selected and scanned. Intermediate splints (ISs) and final splints (FSs) with 2-mm, 3-mm, 4-mm, and 5-mm OCDs were fabricated and grouped as IS-2, IS-3, IS-4, IS-5, FS-2, FS-3, FS-4, and FS-5, respectively. The dentitions were occluded with each splint and scanned as a whole to compare with the original occlusion. Translational and rotational deviations of the lower dentition and translational deviations of the landmarks were measured. Results For vertical translation, the lower dentitions translated inferiorly to the upper dentition in most of the splints, and the translation increased as OCD got larger. Vertical translations of the dentitions in 89.47% of IS-2, 68.42% of IS-3, 42.11% of IS-4, 10.53% of IS-5, 94.74% of FS-2, 63.16% of FS-3, 26.32% of FS-4, and 21.05% of FS-5 splints were below 1 mm, respectively. For pitch rotation, the lower dentitions rotated inferiorly and posteriorly in most groups, and the rotation increased as OCD got larger. Pitch rotations of the dentitions in 100% of IS-2, 89.47% of IS-3, 57.89% of IS-4, 52.63% of IS-5, 100.00% of FS-2, 78.95% of FS-3, 52.63% of FS-4, and 47.37% of FS-5 splints were below 2°, respectively. On the other hand, the transversal and sagittal translations, roll and yaw rotations of most groups were clinically acceptable (translation < 1 mm and rotation < 2°). The deviations of ISs and FSs showed no statistical significance at all levels of coverage (P > 0.05). Conclusions A protocol was proposed to generate 3D-printed ISs and FSs with normalized basal planes and standardized OCDs. Deviations of the ISs and FSs were more evident in the vertical dimension and pitch rotation and had a tendency to increase as the OCD got larger. ISs and FSs with both 2-mm and 3-mm OCD are recommendable regarding the precision relative to clinical acceptability. However, considering the fabrication, structural stability, and clinical application, ISs and FSs with 3-mm OCD are recommended for accurate fitting.